Clinical Labor : Tissue Donors and Research Subjects in the Global Bioeconomy - Cooper, Melinda; Waldby, Cathy (Book collections on Project MUSE., 2014)
Forms of embodied labor, such as surrogacy and participation in clinical trials, are central to biomedical innovation, but they are rarely considered as labor. The authors take on that project, analyzing what they call clinical labor and asking what such an analysis might indicate about the organization of the bio-economy and the broader organization of labor and value today.